Data from: The choice of universal primers and the characteristics of the species mixture determines when DNA metabarcoding can be quantitative. - Pinol, Josep; Senar, Miquel Angel; Symondson, William O. C. (Dryad, 2018)
DNA metabarcoding is a technique used to survey biodiversity in many
ecological settings, but there are doubts about whether it can provide
quantitative results, i.e. the proportions of each species in the mixture
as opposed to a species list. While there are several experimental studies
that report quantitative metabarcoding results, there are a similar number
that fail to do so. Here we provide the rationale to understand under what
circumstances the technique can be quantitative. Basically, we simulate a
mixture of DNA of S species with a defined initial abundance distribution.
In the simulated PCR, each species increases its concentration following a
certain amplification efficiency. The final DNA concentration will reflect
the initial one when the efficiency is similar for all species; otherwise,
the initial and final DNA concentrations would be poorly related. Although
there are many known factors that modulate amplification efficiency, we
focused on the number of primer-template mismatches, arguably the most
important one. We used 15 common primers pairs targeting the mitochondrial
COI region and the mitogenomes of ca. 1200 insect species. The results
showed that some primers pairs produced quantitative results under most
circumstances, whereas some other primers failed to do so. Many species,
and a high diversity within the mixture, helped the metabarcoding to be
quantitative. In conclusion, depending on the primer pair used in the PCR
amplification and on the characteristics of the mixture analysed (i.e.,
high species richness, low evenness), DNA metabarcoding can provide a
quantitative estimate of the relative abundances of different species.
R scripts and data filesPinol_etal.zip
Keywords: in silico PCR; Primer bias; Diet Analysis